Proposed Business Strategy Improvement Through Service Quality Gap Model to Increase Membership Coverage of BPJS Ketenagakerjaan - Harimukti Wandebori (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2019)
BPJS Ketenagakerjaan is a public legal entity based on Law No. 24 of 2011 which is given a mandate by the Government to provide social security protection for all workers in Indonesia. This study aims to find out and improve the BPJS Ketenagakerjaan strategy based on service quality issues. The methodology used in this study using quantitative methods by measuring the service quality gap model to determine the expectations of participants and the ability of the organization to provide services. Secondary data analysis was from company-internal data and literature studies to assess various analysis using methods; such as environmental analysis, SWOT, and TOWS Matrix. The strategy to be implemented is the differentiation strategy. BPJS Ketenagakerjaan needs to create three core competencies, namely reliability, responsiveness, and innovation, to create a superior service quality and added value for customers.